High-current pulsed operation modes of the planar MSS with magnetically insulated anode without transition to the arc discharge - Bizyukov, A.A.; Sereda, K.N.; Sleptsov, V.V.; Tarasov, I.K.; Chunadra, A.G. (Вопросы атомной науки и техники, 2012)
In this work, the characteristics of high-current operation modes of planar magnetron sputtering system with magnetically insulated anode without going to the arc discharge mode is investigated. The possibility of using an additional spatially modulated magnetic field in the anode region to prevent a transition from the magnetron to the arc is shown experimentally. It is shown that the use of such a magnetic field configuration provides efficient interruption of the arc current without external forced shutdown of the discharge. Исследованы особенности сильноточных режимов работы планарной магнетронной распылительной системы с магнитоизолированным анодом без перехода разряда в дуговой режим. Экспериментально показана возможность использования пространственно-модулированного дополнительного магнитного поля в прианодной области для предотвращения перехода режима работы из магнетронного в дуговой. Показано, что использование такой конфигурации магнитного поля обеспечивает эффективное прерывание дугового тока без принудительного внешнего выключения магнетронного разряда. Досліджені особливості сильнострумових режимів роботи планарної магнетронної розпилювальної системи з магнітоізольованим анодом без переходу розряду в дуговий режим. Експериментально показана можливість використання просторово-модульованого допоміжного магнітного поля в прианодній області для запобігання переходу режиму роботи з магнетронного в дуговий. Показано, що використання такої конфігурації магнітного поля забезпечує ефективне переривання дугового струму без примусового зовнішнього вимикання магнетронного розряду.